Recensiones - Mantilla, Sebastián; S. M. A.,; Aguirre, M.; de Sebastián, Luis (ECA: Estudios Centroamericanos, 1974)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 29, No. 303-304, 1974: 89-102.